Wastewater sludge processing. - Turovskiy, Izrail S., ....-; Mathai, P. K., ....- (New Jersey : Wiley-Interscience, 2006)
Wastewater Sludge Processing provides a rational approach to characterizing wastewater sludge, a comprehensive comparison of sludge processing techniques and technologies, a guide to assist in the selection and design of sludge treatment facilities, and an introduction to innovative sludge treatment technologies.
Keywords: Afvalwaterzuivering